Combining ability analysis for yield and yield contributing traits in sesame (Sesamum indicum L.): Combining ability analysis for yield and yield contributing traits in sesame (Sesamum indicum L.) - S P POLE; A S RATHOD; A P GHADAGE; B KRISHNASRI (Journal of Oilseeds Research, 2023)
Among the parents JLT-07 proved to be good general combiner for the characters viz., number of branches per plant and 1000 seed weight, RT-346 for character plant height, PKDS-11 for days to flowering and CO-1 for maturity and number of capsules per plant, RT-351, GT-10, VRI-2 and TMV-4 for oil content. These seven parents could be utilized in the breeding programme for further improvement.